Trapping and manipulation of microscopic bubbles with a scanning optical tweezer - Jones, P; Stride, E; Saffari, N (2006)
The authors have demonstrated three-dimensional trapping of ultrasound contrast agent microbubbles using a circularly scanning optical tweezers to confine the microbubble in a time-averaged optical potential. They have measured the maximum transverse drag force that may be applied to the trapped microbubble before it escapes and found that this decreases significantly at small trap radii. They explain this in terms of the relative volumes of the microbubble and the trap and anticipate that this feature will be important in experiments involving the insonation of optically trapped microbubbles. © 2006 American Institute of Physics.